DNA imaged on a HOPG electrode surface by AFM with controlled potential - Brett, Ana Maria Oliveira (2005)
Single-molecule AFM imaging of single-stranded and double-stranded DNA molecules self-assembled from solution onto a HOPG electrode surface is reported. The interaction of DNA with the hydrophobic surface induced DNA aggregation, overlapping, intra- and intermolecular interactions. Controlling the electrode potential and using the phase images as a control method, to confirm the correct topographical characterization, offers the possibility to enlarge the capability of AFM imaging of DNA immobilized onto conducting substrates, such as HOPG. The application of a potential of +300 mV (versus AgQRE) to the HOPG enhanced the robustness and stability of the adsorbed DNA molecules, increasing the electrostatic interaction between the positively charged electrode surface and the negatively charged DNA sugar-phosphate backbone.